The Impact of Behavioral Biases with Investment Interest as a Mediating Variabel on Online Investment Decition Making Among Generation Z - Tyara; Pertiwi, Tri Kartika; Warmana, Gede Oka (Management Science Research Journal, 2025)
It is important for Generation Z investors to increase awareness of herding bias and overconfidence bias in order to make more rational investment decisions and reduce the risks associated with impulsive behavior. This research provides valuable contributions to understanding the psychological factors that influence the investment behavior of Generation Z. It emphasizes the importance of recognizing and managing psychological biases in investment decision-making, so they can make more rational and informed decisions, as well as reduce the risk of losses due to impulsive behavior in investments. This study aims to analyze the impact of behavioral biases on investment interest and decisions, focusing on Generation Z as the research sample. The sample consists of 116 respondents, all of whom are individuals from Generation Z. The data analysis technique used is Partial Least Squares (PLS) to test the relationships between variables. The research findings indicate that: (1) herding bias contributes to investment decision-making, (2) overconfidence bias contributes to investment decision-making, (3) herding bias contributes to investment interest, (4) overconfidence bias contributes to individual investment decision-making, (5) investment interest contributes to investment decision-making, (6) herding bias contributes to investment decision-making through investment interest, and (7) overconfidence bias contributes to investment decision-making through investment interest.